Existence of three solutions for a quasilinear elliptic equation involving the p(x)–Laplace operator - Ayazoglu (Mashiyev), Rabil; Avci, Mustafa (Sarajevo Journal of Mathematics, 2024)
In this paper, some existence results are obtained by using a three critical point theorem based on variational principle. In that context, we verify that a quasilinear elliptic equation involving the p(x)-Laplace operator has at least three weak solutions under Neumann boundary condition. 2010 Mathematics Subject Classification. 35J60, 35B30, 35B40